The healthcare technology needs you - Subrata, Sumarno Adi; Bayuo, Jonathan; Sahin, Busra (Universitas Muhammadiyah Magelang, 2021)
The growing evidence and technology in healthcare improve the patient's health across a continuum of services in clinical and community settings. A multidisciplinary team should work in tandem on this phenomenon. Therefore, innovative healthcare technology must be designed intensively to optimize productivity, provide new insight, and support the standard treatment for particular diseases. In the coming years, technology is needed to change the way of caring for the patient. Updated studies should be developed and published focusing on innovative technology, including in Medicine, Nursing, Pharmacy, and other health-related topics. Keywords: healthcare; innovation in technology; patient care; outcomes improvement; chronic illness